PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI DI SITUS E-COMMERCE BUKALAPAK - DERMA H. PANE; TIURNIARI PURBA (JURNAL ILMIAH KOHESI, 2020)
Current technological advances emphasize humen needs, technologies that provide the needs that support the informationtechnology community that are carried out to assist in making business. Online business is very much needed in theactivities of buyer in their daily lives. This study discusses site product quality, service quality, cunsumer confidience inbuying interest on e-commerce sites. The sampling method used is non probability sampling method with accidentalsampling technique. The date collection method uses questionnaire, the sample used in this study amounted to 100respondent who conducted transactions in Bukalapak stores. The date collected in this study were analized by linear multipleregression analysis with the help of SPSS (statistical product and service solution) versi 25. Results Bukalapak, relatedservice quality and significant on buying interest on e-commerce sites, Bukalapak consumer confidence, and significant onbuying interest in the study. On the e-commerce site Bukalapak. product quality, service qulity, consumer trust together havea significant interest in buying interest on the Bukalapak e-commerce site.